Stunting Prevention Education Strengthening Program in Simalanggang Village: Efforts to Create a Healthy Generation - Indra Yeni; Afifah Alya Syafira; Hani Zulmeirita Rizki; Meisya Nadhira Azhari; Sandy Kurniawan; Sarah Amelia Lubis (Konsienti : Community Services Journal, 2026)
This activity is an effort to strengthen stunting education in the Simalanggang community as a strategy to create a healthy generation. Stunting, a chronic nutritional problem caused by long-term nutritional deficiencies, is a serious challenge that impacts children's physical and cognitive development. Through a community empowerment approach, education, and the involvement of Padang State University Community Service Program students as educators and community leaders. The results of the stunting education activity in Simalanggang Village show an increase in community knowledge about the importance of stunting prevention as well as maternal nutrition, parenting patterns, and good sanitation. This activity is expected to be an effective first step in eradicating stunting and building a healthier generation in Simalanggang Village.